2014
DOI: 10.1007/s10616-014-9831-z
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypical and functional characteristics of mesenchymal stem cells derived from equine umbilical cord blood

Abstract: Mesenchymal stem cells (MSCs) offer promise as therapeutic aid in the repair of tendon and ligament injuries in race horses. Fetal adnexa is considered as an ideal source of MSCs due to many advantages, including non-invasive nature of isolation procedures and availability of large tissue mass for harvesting the cells. However, MSCs isolated from equine fetal adnexa have not been fully characterized due to lack of species-specific markers. Therefore, this study was carried out to isolate MSCs from equine umbil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…Various neonatal tissues have been described to isolate MSCs in horse, including umbilical cord blood (UCB-MSCs) 8 11 , umbilical cord matrix (UCM-MSCs), commonly referred as “Wharton’s jelly” 12 , amniotic tissue 13 , or placenta 14 . Such cells meet the standards recommended by the International Society of Cellular Therapy (ISCT) for MSCs 15 , including plastic adherence, multilineage differentiation potential, and a particular immunophenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Various neonatal tissues have been described to isolate MSCs in horse, including umbilical cord blood (UCB-MSCs) 8 11 , umbilical cord matrix (UCM-MSCs), commonly referred as “Wharton’s jelly” 12 , amniotic tissue 13 , or placenta 14 . Such cells meet the standards recommended by the International Society of Cellular Therapy (ISCT) for MSCs 15 , including plastic adherence, multilineage differentiation potential, and a particular immunophenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Further work may demonstrate whether changes in electrospun scaffold design can influence diseased tendon cells to express healthy tendon matrix proteins such as type I and type III collagen. We found no significant difference between the groups in the expression of type VI collagen, scleraxis or tenomodulin (data not shown) after 7 d of in vitro culture (Shukunami et al, 2006). This study was limited to early in vitro outcomes and more comprehensive study is required to investigate the effect of biophysical stimulation on extracellular matrix production.…”
Section: Discussionmentioning
confidence: 86%
“…Flow cytometry offers one way in which fibroblasts can be sub-classified. However, previous studies have so far revealed only a handful of cell surface proteins that are preferentially expressed on fibroblasts as opposed to other derivatives of mesenchymal stem cells (Cappellesso-Fleury et al, 2010;Halfon et al, 2011;Mohanty et al, 2014). These include CD106, CD26, CD10 and CD9.…”
Section: Discussionmentioning
confidence: 99%
“…A medula óssea foi a primeira fonte estudada na Medicina para isolamento de CTMs, posteriormente, outras tecidos demonstraram a presença de tais células, como no tecido Em equinos as CTMs foram obtidas a partir da medula óssea, tecido adiposo (DE MATTOS CARVALHO et al, 2009), cordão umbilical (TOUPADAKIS et al, 2010RANERA et al, 2011;CARRADE HOLT et al, 2012;BARBERINI et al, 2014), sangue do cordão umbilical (KOCH et al, 2007;MOHANTY et al, 2014) Em cultura a característica morfológica de CTMs é apresentada com crescimento em monocamada (PITTENGER et al, 1999), aderência ao plástico, aparência fibroblastóide ou fusiforme e células alongadas (KOCH et al, 2007;LOVATI et al, 2011), com núcleo eucromático, oval grande e central, nucléolo proeminente, associado a um abundante citoplasma, observado à microscopia. Maiores detalhes são detectados com microscopia eletrônica, exibindo organelas bem desenvolvidas incluindo, mitocôndrias, complexo de Golgi, lisossomos, vacúolos lipídicos cheios ou vazios, grande quantidade de ribossomos livres no citoplasma e retículo endoplasmático rugoso dilatado, além de filamentos de actina organizados em suas extremidades (TAGAMI et al, 2003).…”
Section: Diagnóstico Por Imagemunclassified